Pengaruh Strategi Bauran Pemasaran Digital Terhadap Keputusan Pembelian Baju Bekas Impor (Studi Kasus Pada Thrift Shop Dolopo) - Saputra, Rajes Sumbowo; Faujianto, Samsu Anhari; Susanto, Andik; Rohmatiah, Ahadiati (Universitas Muhammadiyah Gresik, 2024)
Background – The background of this research focuses on the influence of digital marketing mix strategies on purchasing decisions for imported used clothes, with a case study at Thrift Shop Dolopo. In recent years, there has been a significant change in consumer behavior triggered by the development of digital technology and social media. This phenomenon creates new opportunities for businesses, especially in the clothing sales sector, which is now increasingly dependent on digital platforms to reach customers. Objective – The purpose of this study is to analyze the influence of digital marketing mix strategies on purchasing decisions for imported used clothes, focusing on Thrift Shop Dolopo. This study is expected to provide useful recommendations for Thrift Shop Dolopo in formulating more effective marketing strategies. Design / Methodology / Approach – The methodology of this research was conducted using a descriptive explanatory survey method. The sampling technique used the probability sampling method with the concept of proportional simple random sampling. The research data were obtained primarily by distributing questionnaires to consumers of Thrift Shop Dolopo. Data analysis was carried out using the regression method with the SPSS program version 24 for Windows. Findings – The research results show that separately the product variable can have an influence of 84.2%, the price variable is 95.1%, the place variable is 96.7%, and the promotion variable is 30.4% on purchasing decisions. Meanwhile, together the product, price, place and promotion variables can have an influence of 98.6% on increasing purchasing decisions. This means that marketers need to combine marketing strategies to increase product sales. Research Implication – This study provides deeper insight into how elements in the digital marketing mix (product, price, place, and promotion) interact with each other and influence consumer purchasing decisions. These findings can be a reference for historians and practitioners to formulate more effective marketing strategies. And this study can be the basis for further research in the field of marketing management, especially regarding the digital marketing mix. Limitations – This study was only conducted in Thrift Shop Dolopo, so the results may not be generalized to all thrift shops or imported used clothing businesses in other areas. Differences in demographics and consumer behavior in different locations can affect purchasing decisions. This study only explored four elements in the digital marketing mix. This limits a comprehensive understanding of the factors that influence purchasing decisions.